Parents' Educational Expectations: Does It Matter for Academic Success? - Lindberg, E.nihal; Yıldırım, Erdal; Elvan, Özlem; Öztürk, Dürdane; Recepoğlu, Serpil (SDU International Journal of Educational Studies, 2019)
Previous studies showed that high parental expectations are linked to student motivation to achieve in school, social resilience, aspirations to attend college, high grades, to achieve high scores on standardized tests, and persist longer in school. Adding to these direct effects, parent expectations have been stated as affecting student outcomes indirectly through parental beliefs and perceived efﬁcacy in providing academic support to their children. In this study, it was aimed to examine the parental expectations of their youths’ academic success and future educational career. Thirty-five mothers and 15 fathers whose children were in the eighth grade were interviewed. In the semi-structured interview, fifty parents were asked the factors affecting their expectations, if they share their expectations with their youths, if there are any differences between parents’ and youths’ own expectations. Thematic analysis technique was applied to the transcribed data. The results showed that although there were differences between expected and current situation of academic success of youths, parents mentioned their expectation that their youths’ academic success will be good because of the youths’ own ability or effort. On the other hand, parents’ expectation is not based on the current situation of the youth’s academic success but based on the parents’ aspiration.
Keywords: Academic success,Parental expectation,Parental aspirations,Educational career of youths; 4. Education